2011
DOI: 10.1016/j.bpj.2011.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Rate of Conjugal Plasmid Transfer in a Bacterial Population Using Quantitative PCR

Abstract: Horizontal transfer of genes between species is an important mechanism for bacterial genome evolution. In Escherichia coli, conjugation is the transfer from a donor (F(+)) to a recipient (F(-)) cell through cell-to-cell contact. We demonstrate what we believe to be a novel qPCR method for quantifying the transfer kinetics of the F plasmid in a population by enumerating the relative abundance of genetic loci unique to the plasmid and the chromosome. This approach allows us to query the plasmid transfer rate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…Indeed, more recent studies have found that F plasmid-mediated conjugation readily occurs in E . coli at the 120 rpm shaking speed of the STLE, albeit under different conditions [ 32 , 33 ]. We found sequencing reads that map to the entire F plasmid in both Ara–3 clones, but not in any other clones we sequenced ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, more recent studies have found that F plasmid-mediated conjugation readily occurs in E . coli at the 120 rpm shaking speed of the STLE, albeit under different conditions [ 32 , 33 ]. We found sequencing reads that map to the entire F plasmid in both Ara–3 clones, but not in any other clones we sequenced ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the detection must be sensitive enough to capture events occurring at low frequencies. Nucleic acid measurements, such as qPCR, can also be used in measuring the conjugation efficiency in certain systems [107]; this type of quantification does not require transconjugant enrichment (e.g. by selection), and could circumvent biases introduced by growth.…”
Section: Experimental Platforms To Measure Conjugationmentioning
confidence: 99%
“…The qPCR assays were used to quantify bacterial amount at every time point, using the genetic locus TolC of the bacteria [ 44 ] and Power SYBR ® Green Master Mix (Applied Biosystems, Foster, CA, USA) in an Applied Biosystems 7300 (Applied Biosystems, Foster, CA, USA). Lysed and frozen aliquots of the bacteria (2 μL) were used as templates for the qPCR reactions (20 μL).…”
Section: Methodsmentioning
confidence: 99%
“…The qPCR conditions were as follows: an initial denaturation at 95 °C for 30 s; 40 cycles of 95 °C for 5 s; 60 °C for 60 s. We set the following mathematical model to analyze the effect of ferric oxide nanoparticles on bacterial growth. As batched bacterial cell cultures were assayed, we assumed a logistic bacterial growth, as described previously [ 44 , 45 ]. The logistic model states that the number of cells in a state as a function of time ( N ′) is the product of the growth rate ( ψ ), the number of cells currently in that state ( N ), and the saturation limit of the media ( K ).…”
Section: Methodsmentioning
confidence: 99%